Persepsi Mahasiswa Tentang Efektivitas Program ESP di Fakultas Pertanian Terhadap Peningkatan Kamampuan Bahasa Inggris Mahasiswa - Afendi Afendi; Fahmi Yahya; Darmanto; Abdul Rahim (Jurnal Kependidikan Media, 2026)
This study aims to examine students' perceptions on the effectiveness of English for Specific Purposes (ESP) program to improve English language skills at the Faculty of Agriculture, Samawa University. A mixed-method approach with a sequential explanatory design was employed, started with quantitative data collection using a Likert-scale questionnaire administered to 107 students (from 129 students), followed by semi-structured interviews with 12 purposively selected informants. Four indicators were assessed: relevance of ESP materials, teaching methods, lecturers' ability to use learning media, and lecturers' discipline. The results showed that students' perceptions were generally in the high category (mean total = 3.24 on a scale of 1–4). The indicator of material relevance to agriculture obtained the highest score (mean = 3.42; very high), while the teaching methods indicator obtained the lowest score (mean = 3.10; high). Qualitative findings revealed that students appreciated the lecturers' mastery of content and use of learning media, but complained about teacher-centered teaching methods, lack of strict enforcement of rules, and limited applicative activities outside the classroom. Students recommended the addition of real projects such as interviewing farmers, making presentations, and involving native speakers. The study concludes that the ESP program at the Faculty of Agriculture, Universitas Samawa is perceived as effective, but there remains a gap between students' expectations of applicative learning and classroom realities, necessitating improvements in teaching methods toward more learner-centered and authentic task-based approaches.